2022
DOI: 10.1037/met0000387
|View full text |Cite
|
Sign up to set email alerts
|

A regularization method for linking brain and behavior.

Abstract: In a world of big data and computational resources, there has been a growing interest in further validating computational models of decision making by subjecting them to more rigorous constraints. One prominent area of study is model-based cognitive neuroscience, where measures of neural activity are explained and interpreted through the lens of a cognitive model. Although some early work has developed the statistical framework for exploiting the covariation between brain and behavior through factor analysis l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
7
1
Order By: Relevance
“…We found that there were no strong relationships between the parameters both within-component and between the neural and behavioral parameters. The factor loading estimates in our results do not resemble the loadings found in Turner, Wang, and Merkle (2017) and Kang et al (2021), where we can see the extent of the potential bias of the loadings estimates resulting from data pooling, which also fails to account for individual differences in the data. Additionally, the true relationship between the neural and behavioral parameters is likely obscured because of the low number of trials per participant.…”
Section: Application 3: Neural and Behavioural Datacontrasting
confidence: 99%
See 3 more Smart Citations
“…We found that there were no strong relationships between the parameters both within-component and between the neural and behavioral parameters. The factor loading estimates in our results do not resemble the loadings found in Turner, Wang, and Merkle (2017) and Kang et al (2021), where we can see the extent of the potential bias of the loadings estimates resulting from data pooling, which also fails to account for individual differences in the data. Additionally, the true relationship between the neural and behavioral parameters is likely obscured because of the low number of trials per participant.…”
Section: Application 3: Neural and Behavioural Datacontrasting
confidence: 99%
“…Evidently, the method shares many parallels with joint-modelling work by Turner, Wang, and Merkle (2017), however, it extends on this approach by offering a more flexible, hierarchical sampling method, which draws strengths from state of the art Bayesian estimation techniques (namely PMwG; Gunawan et al, 2020). Further, methods by Kang et al (2021) that build on the factor analysis methods of Turner, Wang, and Merkle (2017) by including Lasso priors, could also extend to the current methods. Whilst the initial methods of Turner, Wang, and Merkle (2017) are useful for estimating factor loadings of neural activity related to the NDDM (Turner, Van Maanen, & Forstmann, 2015), PMwG-FA allows model estimation with a factor analysis Gibbs step, in a Bayesian hierarchical framework, to be applied to any statistical model (where estimating the likelihood is possible).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These neuro-cognitive models utilize trial-or individual-level signatures of EEG or magnetoencephalography (MEG) signals to assess, constrain, replace, or even add cognitive parameters in models (Nunez et al, 2017(Nunez et al, , 2022. Moreover, Turner et al have proposed many approaches for directly or indirectly relating neural data to a cognitive model; for instance, the field of model-based cognitive neuroscience has used BOLD responses and EEG waveforms simultaneously and separately to predict and constrain cognitive parameters and behavioral data (Turner et al, 2013(Turner et al, , 2016(Turner et al, , 2019Bahg et al, 2020;Kang et al, 2021). Also, Nunez et al have introduced some neuro-cognitive models to study the effect of selective attention, the role of visual encoding time (VET), and the relationship of readiness potentials (RPs) in motor cortical areas to evidence accumulation during perceptual decision-making tasks (Nunez et al, 2017(Nunez et al, , 2019Lui et al, 2021).…”
Section: Introductionmentioning
confidence: 99%